(untitled) (Journal of Hama University, 2024)
This research was carried out at the Agricultural Scientific Research Center in Al-Ghab during the agricultural season (2020/2021)to study the effect of plant density on the growth and yield of the peanut crop.Three planting distances D1 (75 x 15 cm), D2 (75 x 20 cm), and D3 (75 x 30 cm) were tested in a Randomized Complete Block Design (RCBD) with three replication. the results showed that there were significant differences between the studied distances, the distance D1 (75 x 15 cm) was significantly superior in average plant height (39.17 cm) and average seed yield ( 3560 kg ha-1), while there were no significant differences between the studied densities in the average number of main branches per plant, D3 density (75×30 cm) was significantly superior in the mean number of pods per plant (35.38 pods per plant-1) and weight Pods per plant (73.44 g. plant-1), and the average weight of one hundred seeds (90.33 g). Therefore, it is recommended to plant the peanut crop at a distance of (75×15 cm) to obtain the highest seed yield, and to plant at a distance of (75×30 cm) to obtain large seeds.